Lifelong Learning and Adaptive Expertise in Faculty Development Programs - Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2025)
Medical knowledge doubles every year, meaning that much of what was learned during formal education will eventually become outdated. It is important for faculty to continue to update their own expertise to reflect current best evidence-based practices and technologies. Embedding these principles keep educators versatile, creative, and successful throughout their careers. This lifelong learning commitment by faculty fosters a similar mindset among students, which is an important part of navigating a profession where learning is a lifetime process. Faculty are more than sources of information; they represent role models for the next generation. The institutions have an important role in supporting the faculty by recognizing and rewarding their professional growth. Understanding those faculties who attend conferences, certification, or contribute to medical education research will create an enabling environment. Learning communities or journal clubs focusing on innovations in medical education also advance collaboration and learning.